What is the nature and extent of student-university mismatch? - Gillian Wyness; Richard Murphy (IZA World of Labor, 2020)
A growing body of research has begun to examine the match between student ability and university quality. Initial research focused on overmatch—where students are lower attaining than their college peers. However, more recently, attention has turned to undermatch, where students attend institutions with lower attaining peers. Both have been shown to matter for student outcomes; while in theory overmatch could be desirable, there is evidence that overmatched students are less likely to graduate college. Undermatched students, meanwhile, have been shown to experience lower graduate earnings.
Keywords: I22; I23; I28; 330; student ability; university quality; higher education